Deep learning for urban land use category classification: A review and experimental assessment - Li, Ziming; Chen, Bin; Wu, Shengbiao; Su, Mo; Chen, Jing M.; Xu, Bing (Remote sensing of environment, 2024)
Mapping the distribution, pattern, and composition of urban land use categories plays a valuable role in understanding urban environmental dynamics and facilitating sustainable development. Decades of effort in land use mapping have accumulated a series of mapping approaches and land use products. New trends characterized by open big data and advanced artificial intelligence, especially deep learning, offer unprecedented opportunities for mapping land use patterns from regional to global scales. Combined with large amounts of geospatial big data, deep learning has the potential to promote land use mapping to higher levels of scale, accuracy, efficiency, and automation. Here, we comprehensively review the advances in deep learning based urban land use mapping research and practices from the aspects of data sources, classification units, and mapping approaches. More specifically, delving into different settings on deep learning-based land use mapping, we design eight experiments in Shenzhen, China to investigate their impacts on mapping performance in terms of data, sample, and model. For each investigated setting, we provide quantitative evaluations of the discussed approaches to inform more convincing comparisons. Based on the historical retrospection and experimental evaluation, we identify the prevailing limitations and challenges of urban land use classification and suggest prospective directions that could further facilitate the exploitation of deep learning techniques in urban land use mapping using remote sensing and other spatial data across various scales. •A review in the field of deep learning for urban land use classification•A comprehensive overview of various deep learning model architectures•Eight comparative experiments considering data, samples, and model variations•Challenges and opportunities in deep learning-driven urban land use classification